Analisis Maturitas dan Kerangka Governance, Risk, And Compliance (GRC) Upaya Peningkatan Pendapatan Asli Daerah atas Pengelolaan Kekayaan yang Dipisahkan di Provinsi DKI Jakarta: Studi Kasus PT. Bank DKI Tahun 2018-2022 - Ningrat, Murtadhi Achmad; Suwanda, Dadang; Huseno, Tun (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
In Local Government there is a local revenue that should be a source of local finance in the exercise of regional autonomy. This phenomenon has occurred since the regulation on regional autonomy was formed. Local revenue is divided into several sub income, which include the wealth of the separated regions. The source is from each regional owned enterprises. Bank Bank DKI is one of the regional owned enterprises that are accommodated in BP BUMD, because part of its ownership stake is in the Provincial Government of DKI Jakarta. Bank DKI must be able to provide dividends and on the one hand must provide adequate business, without being hindered by anything and this is the problem in this study. For this reason, BUMD must be able to balance these problems through the concept of GRC Excellence Framework and maturity analysis. This study is limited to assessing local revenue through the concept of GRC excellence framework, along with its maturity level. The purpose of this study is to determine how the level of maturity owned by Bank DKI in terms of internal organization as a whole, and its benefits for the Provincial Government of DKI Jakarta. This study used descriptive qualitative methods. This study analyzes the level of maturity in each component of the advantages of GRC contained in bank dki and the impact of these advantages will seek to increase local revenue with the distribution of dividends accompanied by maturity analysis. Data collection techniques in this study using observation techniques, interviews, documentation. Researchers use data analysis techniques such as data reduction, data presentation, and conclusion. In testing the validity of the data researchers used triangulation sources. The results showed that the existing system of each GRC excellence criteria include: Process aspects, People aspects, Tools aspects, which are very varied levels of maturity. However, the average level is still in Managed with a score of 3. With good governance, there are several aspects of process and aspects of people that need to be recommended for the future. For local revenue for the last 5 years from 2018-2022, it has experienced significant fluactation due to the lack of massive implementation and implementation of the GRC concept, which makes governance no significant improvement.